Problematika Pengelolaan dan Pengembangan Tanah Wakaf - Wildan Mukhalad (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2020)
Waqf is a very noble deed. Each waqf property must be managed and developed in accordance with the philosophical values of wisdom, which is to be good for social life and charity that always flows to the waqf. Such a goal, will not be achieved if the management of waqf is contrary to Islamic law and legislation, such as the management that occurred in Meureubo District caused a lot of problems. Therefore, this study formulates the management of waqf land, obstacles, and strategies for developing waqf land in Meureubo Sub-district, West Aceh District. This research is qualitative descriptive with a case study method or approach, carried out at KUA and Meureubo District communities. Data collection technique’s through interviews is observation and documentation. Data analysis techniques are carried out by data reduction, data presentation, and data verification to formulate the concept of findings based on waqf management theory. The result of the research shows that: (1) Management of waqf land management in Meureubo is not implemented well, because the manager is in the form of an individual. This form does not give birth to two management indicators that are: planning and organizing. (2) Obstacles in the management of waqf land are lack of community understanding about waqf, lack of awareness of wakif and nazir waqf, weak government institutional role, low-quality human resources, and lack of supervision. (3) The strategies are a) synergy between agencies or institutions, b) socialization of the representatives, c) improvement of the quality of the waqf ruling.